2011
DOI: 10.1007/s10072-011-0691-4
|View full text |Cite
|
Sign up to set email alerts
|

Section of the filum terminale: is it worthwhile in Chiari type I malformation?

Abstract: A section of the filum terminale (SFT) is used for the surgical treatment of isolated tethered cord or that resulting from neurulation disorders. More recently, it has been proposed for the management of the occult tethered cord syndrome (OTCS), though it is still under debate. Even more controversial appears to be the use of SFT in patients with Chiari type I malformation (CIM), which is based on the possible presence of OTCS. This review shows that: (1) there are issues both in favor and against the occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 14 publications
0
20
0
1
Order By: Relevance
“…12,28,36 Another group has found no correlation between tethered cord and CM-I. 25 After efforts to exclude CM-II patients with myelomeningocele, we found a small number of patients who had undergone a spinal cord untethering operation in addition to CMD. Although the overall numbers were small and the difference was not statistically significant, there was a trend toward an increasing frequency of untethering procedures, with 6 performed in the first half of the study period compared with 17 in the second half.…”
Section: Tethered Cordmentioning
confidence: 79%
“…12,28,36 Another group has found no correlation between tethered cord and CM-I. 25 After efforts to exclude CM-II patients with myelomeningocele, we found a small number of patients who had undergone a spinal cord untethering operation in addition to CMD. Although the overall numbers were small and the difference was not statistically significant, there was a trend toward an increasing frequency of untethering procedures, with 6 performed in the first half of the study period compared with 17 in the second half.…”
Section: Tethered Cordmentioning
confidence: 79%
“…Alterations in this anchoring can increase tension on the caudal spinal cord with clinical consequences, so‐called tethered cord syndrome (TCS) in people . There is an association among a subset of CM1 patients, as well as those suffering from SM, with TCS . To date, the relationship between Chiari malformations, syringomyelia (CMSM) and TCS has not been explored in dogs; although, a recent study using a 3‐dimensional computer model suggested tethering as a potential mechanism for SM development within the canine spinal cord …”
Section: Introductionmentioning
confidence: 99%
“…While Milhorat et al have suggested there may be a link between a Chiari I malformation and tethered cord, 9 several studies have suggested against such an association. [10][11][12] Thereby, the authors attribute the dry lumbar thecal sac to chronic CSF over-drainage.…”
Section: Resultsmentioning
confidence: 99%